Arroz negro (oryza sativa L.): caracterização das frações de extrato e avaliação dos efeitos da radiação ionizante na composição, propriedades físico-químicas, térmicas, estruturais e atividade antioxidante - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
Black rice is a variety of pigmented rice. It contains numerous nutritional and bioactive components, including essential amino acids, functional lipids, dietary fibre, vitamins, minerals, anthocyanins, phenolic compounds, γ-oryzanols, tocopherols, tocotrienols, phytosterols and phytic acid. Chapter I focus on the production and consumption of rice, as well as historical aspects, alternative agronomic strategies and chemical composition, nutritional and functional properties, applications and technologies/treatments of black rice. The aim of chapter II was performed to evaluate the physicochemical, thermal, crystallographic and morphological properties of biodynamic black rice starch, and of the residual fractions from aqueous extraction. The contents of ash, dietary fibre, proteins and lipids in the starch were lower than those from the residual fractions. All the samples had clear A-type diffraction patterns, with main reflections at 2θ ≈ 15°, 17°, 18° and 23°; they also presented a similar crystallinity index (~22%). Micro-images showed polyhedral starch granules having irregular shapes, with sharp angles and edges, and without pores on the smooth surface. In chapter III, the effects of different doses of gamma radiation (0, 1, 2 e 3 kGy) on the thermoanalytical, structural and pasting properties of black rice flour were observed using thermogravimetry and derivative thermogravimetry (TG-DTG), differential scanning calorimetry (DSC), X-ray diffraction (XRD), field emission gun-scanning electron microscopy (FEG-SEM), particle size distribution and pasting properties (RVA) analysis. The irradiated samples showed a decrease in all the thermal parameters, gelatinisation enthalpy, degree of relative crystallinity and pasting properties. After gamma radiation some changes occurred, such as cracks, pores and a decrease of mean size of the granules. Chapter IV investigated the effects of gamma radiation to evaluate the stability and thermal degradation kinetics of total anthocyanins content (TAC), as well as the stability of total phenolic compounds (TPC) and antioxidant activity at different temperatures (4, 25, 35 and 45 °C) during the storage (120 days) of black rice flour. At time 0, the dose of 3 kGy provided all of the most available bioactive compounds, except for TPC. During the storage at different temperatures up to 120 days, gradual losses occurred in all the analysed parameters. Regarding the TAC and TPC, the sample irradiated with a 1 kGy dose remained most stable. The analysis of kinetic data indicated a first-order reaction for the degradation of anthocyanins. In chapter V, the effects of gamma radiation on the antioxidant activity of the free and bound total phenolics, physicochemical and microbiological properties of black rice flour samples during storage were evaluated. A chemometric approach made it possible to observe the effects of irradiation and storage time on the samples. Regarding bioactive compounds, with the exception of the bound phenolic fractions the 3 kGy dose showed the highest values at time 0. At 120 days there was a decrease in these levels for all the samples. Regarding the attribute of colour, the irradiation slightly modified all the parameters; in terms of microbiological analysis there was no growth of microorganisms at the end of storage. The nutritional value of black rice means that it has the potential to be used in the production of healthy foods and beverages, such as functional products and gluten-free cereals. Therefore, the combination of irradiation with different temperatures may improve the shelf-life of black rice flour.
Keywords: Amidos; Compostos bioativos; Estabilidade; Farinhas; Processos ambientalmente amigáveis; Bioactive compounds; Environmentally friendly processes; Flours; Stability; Starches; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS